Temperantia, stoicki złoty środek według Seneki Młodszego - Budzanowska, Dominika (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2011)
Seneca’s philosophical writings concern a virtue, among others also the virtues of justice, temperance (or moderation), fortitude and prudence. They are four virtues from the time of St. Ambrose called cardinal. Seneca gives this definition of the virtue temperantia: cupiditates refrenare – to confine one’s desires. So the temperance is practicing self-control, abstention and moderation. Seneca discuses it very often in a wider context of the different virtues, with which it’s tightly connected according to a stoical idea of the inseparability of the virtues. He claims that we have to learn virtue. Seneca reminds, that the life is not easy and only the indications of the philosophy concerning virtue preserve from the unjust fortune.
Temperantia, golden mean of Seneca the Younger, Roman Stoic
Temperantia , стоиЦкая „золотая Середина” по Сенеке
Сенека, будучи последователем и представителем философской школы младшей стои, склонялся к эклектике и ставил этику на первый план. Его философские сочинения посвящены вопросам практической морали. Он стремился дать людям утешение посредством житейской мудрости. Цель человека заключается в том, чтобы „жить в согласии с природой”. Сенека учил как жить и поэтому много писал о добродетелях. Философ хотел, чтобы император и каждый человек обладал такими качествами, как: воздержанность, мужество, разумность, справедливость и чтобы знал, что добродетель „следует обуздать желания, подавить боязнь, разумно заботиться о предстоящих делах, раздать всё, что должно быть отдано”. Сенека учил: „Воздержность умеряет наслажденья; одни она с ненавистью изгоняет, другие соразмеряет и сокращает до здорового предела, никогда не приближаясь к ним ради них самих. Она знает, что лучшая мера для всего желанного – взять не сколько хочется, а сколько необходимо”.
Keywords: Seneca the Younger; Philosophy; Stoicism; Virtue; Temperance (moderation); Desires